Co-viewers support participation in video chat interactions, but live experiences promote richer word learning for 24- to 36-month-olds in the USA. Issue 4 (2nd October 2019) - Myers, Lauren J.; Keyser, Heather; Cors, Mary
ABSTRACT: The 2016 recommendations by the American Academy of Pediatricsto limit screen time for young children now provide exceptions for moderate video chat usage. We tested whether co-viewer supported face-to-face live interactions uniquely promote 24- to 36-month-old children's participation and learning compared to co-viewer supported on-screen video chat interactions. An adult co-viewer explained the relevance of a social partner's information and helped children see the partner as connected to real events and objects. Results showed that the partner condition impacted learning: children learned and transferred more novel words in the live condition compared to the video chat condition, and this difference was greatest for younger children. However, children participated similarly with live and video chat partners: there were no differences in imitating actions and responding promptly to the partner's bids. Results therefore demonstrated that even when children experience media with a supportive co-viewer and even when they interact with the on-screen information, they nevertheless learn more from live interactions compared to video chat interactions.